2019
DOI: 10.1021/acs.jpclett.9b01468
|View full text |Cite
|
Sign up to set email alerts
|

Anticrossing of Longitudinal and Transverse Modes in Simple Fluids

Abstract: If interacting modes of the same symmetry cross, they repel from each other and become hybridized. This phenomenon is called anticrossing and is well-known for mechanical oscillations, electromagnetic circuits, waveguides, metamaterials, polaritons, and phonons in crystals, but it still remains poorly understood in simple fluids. Here, we show that structural disorder and anharmonicity, governing properties of fluids, lead to the anticrossing of longitudinal and transverse modes, which is accompanied by their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 63 publications
2
41
0
Order By: Relevance
“…The value of q-gap (characterizing transverse excitations at small q) has been assumed [30,41,42] to influence the heat capacity of fluids, but this has never been tested directly in either experiments or MD simulations. Another generic phenomenon recently studied with MD simulations, theoretically, and experimentally with the model fluids [21,43] is anticrossing of longitudinal and transverse excitations. It has been demonstrated that structural disorder and ahnarmonicity induce mutual mixing of the modes at large q.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The value of q-gap (characterizing transverse excitations at small q) has been assumed [30,41,42] to influence the heat capacity of fluids, but this has never been tested directly in either experiments or MD simulations. Another generic phenomenon recently studied with MD simulations, theoretically, and experimentally with the model fluids [21,43] is anticrossing of longitudinal and transverse excitations. It has been demonstrated that structural disorder and ahnarmonicity induce mutual mixing of the modes at large q.…”
mentioning
confidence: 99%
“…The excitation spectra were calculated with the methods developed in Refs. [32,43]. At the first step, we calculated particle current spectra C L,T (q, ω) [38]:…”
mentioning
confidence: 99%
See 3 more Smart Citations